A Spanish contribution to the development of the English interlude: From Rojas' La Celestina to Rastell's Calisto and Melebea. Issue 2 (2nd April 2020) - Ruiz-Moneva, María Ángeles
Abstract: The interlude has traditionally been regarded as one of the earliest manifestations of English Renaissance drama. This essay contends that, like much English literature of the time, it was also open to the influence of foreign literatures and analyses how the author of the interlude known as Calisto and Melebea, attributed to John Rastell (ca.1525), adapts the Spanish work La Celestina. Tragicomedia de Calisto y Melibea, by Fernando de Rojas (ca.1499/1502-1514). The writing of this interlude relies not only upon the evolution of English forms and genres but also upon the influence of its Spanish literary origin. A close reading demonstrates that the genre of the original work is adapted to the conventions of the English interlude.